A Case of Myotonic Dystrophy Type I With Rimmed Vacuoles in Skeletal Muscle Pathology. (December 2021) - Ban, Rui; Zhang, Yutong; Li, Ke; Shi, Qiang
Abstract : Abstract: Dystrophia myotonica type 1 (DM1) and DM2 are the most common muscular dystrophies. In both diseases, the skeletal muscle is the most severely affected. Additional symptoms are also involved in the eye, heart, brain, endocrine glands, gastrointestinal tract, skin, skeleton, and peripheral nerves. Skeletal muscle pathology is mainly manifested as myopathic changes including internal nuclei, sarcoplasmic masses, preferential type 1 fiber atrophy, and so on. Rimmed vacuoles (RVs) seen on muscle biopsy are areas of muscle destruction with an accumulation of autophagic vacuoles. However, there is no report about RVs in skeletal muscle of myotonic dystrophy patients. Here, we describe the first case of DM1 with RVs in skeletal muscle pathology.